2005
DOI: 10.1111/j.1468-5584.2005.00270.x
|View full text |Cite
|
Sign up to set email alerts
|

Eliciting false memories on implicit and explicit memory tests after incidental learning

Abstract: In a false memory experiment, lists of semantic associates (e.g., newspaper, letter, book, etc.) were presented to three groups of participants to induce false memories for critical nonpresented (CN) words (e.g., read) in an incidental learning task. The control group simply estimated the frequency rate in everyday Japanese discourse of each word on a list. The imagery instruction group received an additional instruction to imagine a thematically related converging word from the target words on a list. Partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
(56 reference statements)
1
3
0
3
Order By: Relevance
“…McKone and Murphy (2000) replicated McDermott's (1997) results and even found that the magnitude of critical lures' priming effect was equivalent to that of studied items. The priming effects of critical lures were also found in other studies involving similar tasks such as a lexical decision task (i.e., to classify stimuli as words or nonwords) (Tajika, Neumann, Hamajima, & Iwahara, 2005;Tse & Neely, 2005.…”
Section: Perceptual Vs Conceptual False Memoriessupporting
confidence: 74%
See 1 more Smart Citation
“…McKone and Murphy (2000) replicated McDermott's (1997) results and even found that the magnitude of critical lures' priming effect was equivalent to that of studied items. The priming effects of critical lures were also found in other studies involving similar tasks such as a lexical decision task (i.e., to classify stimuli as words or nonwords) (Tajika, Neumann, Hamajima, & Iwahara, 2005;Tse & Neely, 2005.…”
Section: Perceptual Vs Conceptual False Memoriessupporting
confidence: 74%
“…According to spreading-activation theories (Howe et al, 2009;Roediger et al, 2001 (McDermott, 1997;Otgaar et al, 2015;Tajika et al, 2005). The discrepancy between previous studies and our study led us to conduct a second experiment where we orthogonally manipulated the modality (picture vs. word) of both the DRM stimuli and the PCT.…”
Section: Resultsmentioning
confidence: 58%
“…Os nossos dados corroboram a possibilidade da activação não consciente dos itens críticos em tarefas perceptivas de completamento de inícios que foi já demonstrada por outros autores (e.g., Hicks & Starns, 2005, Experimento 1;McKone & Murphy, 2000, Experimentos 1 e 3; Smith et al, 2002, Experimentos 2 e 3; Tajika & Hamajima, 2002;Tajika et al, 2005); efeito de primação que nem sempre é obtido quando são usadas tarefas de memória implícita de decisão lexical e de identificação (e.g., McKone, 2004;Zeelenberg & Pecher, 2002, Experimentos 1, 2 e 4), as quais parecem privilegiar, mais ainda, o acesso às características físicas dos estímulos. De notar que a melhoria do completamento de itens críticos e de associados foi comparada com linhas de base para a qual contribuíram as mesmas palavras testadas na nossa experiência.…”
Section: Completamento De Inícios De Palavras Primaçãounclassified
“…Nestes estudos tem sido privilegiado sobretudo, o recurso a tarefas de completamento de palavras (e.g., McDermott, 1997;McKone & Murphy, 2000;Tajika, Neumann, Hamajima, & Iwahara, 2005) e a tarefas de decisão lexical que envolvem a emissão de um juízo quanto ao estímulo apresentado ser uma palavra ou uma não-palavra (e.g., Hancock, Hicks, Marsh, & Ritschel, 2003;McKone, 2004;Zeelenberg & Pecher, 2002).…”
unclassified